2009
DOI: 10.2353/ajpath.2009.090211
|View full text |Cite
|
Sign up to set email alerts
|

Glycosaminoglycan-Mediated Loss of Cathepsin K Collagenolytic Activity in MPS I Contributes to Osteoclast and Growth Plate Abnormalities

Abstract: Mucopolysaccharidoses are a group of lysosomal storage diseases characterized by the build-up of glycosaminoglycans (GAGs) and severe skeletal abnormalities. As GAGs can regulate the collagenolytic activity of the major osteoclastic protease cathepsin K, we investigated the presence and activity of cathepsin K and its co-localization with GAGs in mucopolysaccharidosis (MPS) type I bone. The most dramatic difference between MPS I and wild-type mice was an increase in the amount of cartilage in the growth plates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
74
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(81 citation statements)
references
References 43 publications
6
74
0
1
Order By: Relevance
“…Previous studies have shown that excess GAG accumulation inhibits the degradation of collagen type II by cathepsin K, resulting in impaired osteoclast activity and decreased cartilage resorption. This contributes to the skeletal abnormalities seen in the MPS1 human disease and the mouse model 43, 44. Significant normalization of bone volume and density values in our treated mice is further evidence of the therapeutic reduction of systemic GAGs achieved via liver‐directed hAEC transplantation.…”
Section: Discussionsupporting
confidence: 58%
“…Previous studies have shown that excess GAG accumulation inhibits the degradation of collagen type II by cathepsin K, resulting in impaired osteoclast activity and decreased cartilage resorption. This contributes to the skeletal abnormalities seen in the MPS1 human disease and the mouse model 43, 44. Significant normalization of bone volume and density values in our treated mice is further evidence of the therapeutic reduction of systemic GAGs achieved via liver‐directed hAEC transplantation.…”
Section: Discussionsupporting
confidence: 58%
“…2 The storage of GAGS in growing cartilage is thought to cause a bone maturation defect characterized by impaired osteoclast activity and decreased cartilage reabsorption. 16 Closed cephaloceles could represent a further manifestation of the pathologic process that affects the whole skeletal system in MPS. Of note, these abnormalities have been found in sites most frequently involved in skull defects in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…One finding described in several patients with MPS is the presence of pituitary sella abnormalities, found in MPS I, 51 have demonstrated a dysfunction of bone maturation in an MPS animal model, which may account for the above-mentioned skull deformities. Moreover, an enlarged pituitary gland was found in a child with MPS IIIA who had precocious puberty.…”
Section: Other Brain Mr Imaging Findingsmentioning
confidence: 99%
“…51 Thus, spinal MR imaging demonstrates various abnormalities concerning the vertebral bodies and intersomatic disks (Fig 6). Characteristic features are platyspondylia, and bullet shape and beaking of vertebrae, while disks were described as dehydrated.…”
Section: Vertebral and Disk Abnormalitiesmentioning
confidence: 99%